Case Report: Filamin C gene mutation associated with restrictive cardiomyopathy leading to heart transplantation - Sales, Ludmila De Oliveira Jaime; Gutierrez, Paulo Sampaio; Siqueira, Adailson Wagner D.; Jatene, Marcelo Biscegli; Azeka, Estela (Frontiers in Transplantation, 2024)
BackgroundCardiomyopathy is a disease that affects the myocardium and can be classified as dilated, restrictive, or hypertrophic cardiomyopathy. Among the subtypes, restrictive cardiomyopathy is characterized by restriction of ventricular filling and its uncommon cause is a disease due to mutation on Filamin C (FLNC) gene. Filamin C is an actin-binding protein encoded by FLNC gene and participates in sarcomere stability maintenance, which is expressed on the striated muscle. FLNC variants have been associated with restrictive cardiomyopathy and non-compaction cardiomyopathies. The association of FLNC with a broad spectrum of cardiac phenotypes shows an important gap in knowledge. Therefore, a wide investigation is necessary to diagnose this pathology, including an anatomopathological study and genetic tests.Methods/resultsThe purpose of this study is to report about a patient who had restrictive cardiomyopathy due to mutation on Filamin C gene and was indicated for heart transplantation.ConclusionThe etiology of cardiomyopathy is important for the clinical management of the patient and also for guiding families regarding genetic counseling and prevention of new cases in the family.